Maternal Serum Netrin-1 Levels in Pregnancies Complicated by Gestational Diabetes Mellitus - Colak, Busra; Kender Erturk, Nergis; Kartal Golcuk, Esra; Dincgez, Burcu; Erturk, Anil (The European Research Journal, 2026)
Objective: Gestational diabetes mellitus (GDM) is associated with metabolic and vascular disturbances, yet its underlying biological mechanisms remain incompletely understood. Netrin-1, a multifunctional protein involved in angiogenesis, inflammation, and endothelial homeostasis, has been implicated in metabolic disorders; however, clinical data in GDM are limited. This study aimed to evaluate maternal netrin-1 levels in pregnancies complicated by GDM and to assess their associations with clinical parameters. Methods: This prospective case–control study included 45 pregnant women with GDM and 80 healthy pregnant controls between 24 and 28 weeks of gestation. Serum netrin-1 concentrations were measured using enzyme-linked immunosorbent assay. Clinical characteristics, glycemic parameters, and pregnancy outcomes were recorded. Receiver operating characteristic (ROC) analysis assessed the discriminatory performance of netrin-1 for GDM, and correlation and multivariable regression analyses identified associations after adjustment for selected covariates. Results: Serum netrin-1 levels were significantly lower in GDM group compared with controls (P<0.001). Netrin-1 concentrations showed significant inverse correlations with fasting plasma glucose (r=−0.446, P=0.002) and HbA1c (r=−0.623, P<0.001). ROC analysis identified an optimal cut-off value of 0.09 ng/mL for discriminating GDM, yielding a sensitivity of 68.9% and a high specificity of 98.8% (AUC=0.861), indicating good discriminative performance. In multivariable analysis adjusted for age, body mass index, and parity, log-transformed netrin-1 levels were associated with GDM (P<0.001). Conclusion: Maternal netrin-1 levels are significantly reduced in pregnancies complicated by GDM and are closely associated with glycemic dysregulation. Netrin-1 may reflect underlying metabolic and vascular alterations and could be considered as a complementary biomarker rather than a standalone diagnostic tool in GDM.